EFEKTIVITAS BIAYA OPERASIONAL PENDISTRIBUSIAN DANA ZAKAT PADA PROGRAM SENYUM MANDIRI - Muhammad Sakinul Firdaus; Metti Paramita; Tuti Kurnia (JOURNAL ISLAMIC ECONOMICS AD DIWAN, 2023)
Rumah Zakat as one of the leading LAZs in Indonesia has a community economic empowerment program, namely "Senyum Mandiri". This study aims to find out about the operational cost effectiveness of the distribution of ZIS funds in the program which is located in the Bogor area. The method used in this study is to use the Allocation to Collection Ratio (ACR) technique, with the Net ACR formula and the Importance Performance Analysis (IPA) method. The results in this study indicate that the management of the operational costs of distributing zakat funds in the "Smile Mandiri" program was carried out very effectively in the 2018 and 2019 periods, with a respective percentage of 101% in the 2018 period and 105% in the 2019 period. Operational costs of distributing zakat funds is divided into two parts, namely the regular program and the project. The allocation of operational costs is used for the purposes of mobilization, communication and consumption in the distribution process